PENGEMBANGAN ARTIFICIAL INTELLIGENCE BERUPA VIRTUAL ASSISTANT MOBILE MENGGUNAKAN FRAMEWORK FLUTTER - Reyhan Haqiqi Alif Fourniawan; Ade Eviyanti; Suhendro Busono (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Various technologies have been developed today, with Artificial Intelligence (AI) being a prime example. This technology has had a significant impact on our lives, assisting in tasks, jobs, and everyday activities. In this research, an artificial intelligence-based virtual assistant will be developed to facilitate and complete tasks. This artificial intelligence takes the form of a virtual assistant that answers user's questions. This artificial intelligence will be helpful in various fields, including healthcare, economics, education, technology, and more. Additional-ly, the development will focus on a mobile platform to make it user-friendly. Developing an AI-based virtual assistant on a smartphone or mobile platform is highly relevant to the current technological advancements. With this virtual assistant, users can access information or assis-tance anytime, anywhere, making it a practical solution in daily life. Furthermore, in the de-velopment of this virtual assistant, it has already undergone testing using the black-box meth-od. In these tests, the virtual assistant application has successfully passed testing for both its user interface and all of its features.